Association between diabetes and adjuvant chemotherapy implementation in patients with stage III colorectal cancer. Issue 10 (4th June 2022) - Kanehara, Rieko; Goto, Atsushi; Watanabe, Tomone; Inoue, Kosuke; Taguri, Masataka; Kobayashi, Satoshi; Imai, Kenjiro; Saito, Eiko; Katanoda, Kota; Iwasaki, Motoki; Ohashi, Ken; Noda, Mitsuhiko; et al.
Abstract: Aims/Introduction: Among colorectal cancer (CRC) patients, pre‐existing diabetes is suggested to influence poor prognosis, but the impact on adjuvant chemotherapy implementation is largely unknown. We aimed to compare the implementation rate of adjuvant chemotherapy between CRC patients with and without pre‐existing diabetes in a retrospective cohort study. Materials and Methods: Colorectal cancer diagnosis information was obtained from the hospital‐based cancer registry of patients with stage III CRC who underwent curative surgery in 2013 in Japan ( n = 6, 344). Health claims data were used to identify diabetes and chemotherapy. We examined the association between diabetes and the implementation rate of adjuvant chemotherapy using a generalized linear model adjusted for age, sex, updated Charlson Comorbidity Index, hospital type and prefecture. Furthermore, we applied a mediation analysis to examine the extent to which postoperative complications mediated the association. Results: Of the 6, 344 patients, 1, 266 (20.0%) had diabetes. The mean ages were 68.2 and 71.3 years for patients without and with diabetes, respectively. Compared with those without diabetes, patients with diabetes were less likely to receive adjuvant chemotherapy (crude rate 58.9 and 49.8%; adjusted percentage point difference 4.6; 95% confidence interval 1.7–7.5). The difference was evident for patients aged <80 years, and larger for platinum‐containing regimens than others. Mediation analysis showed that postoperative complications explained 9.1% of the inverse association between diabetes and adjuvant chemotherapy implementation. Conclusions: We observed that patients with stage III CRC and diabetes are less likely to receive adjuvant chemotherapy than those without diabetes, and postoperative complications might partially account for the association. Abstract : Preexisting diabetes may interfere with adjuvant chemotherapy for colorectal cancer. The interfering with the therapy is remarkable in platinating agent‐based regimens. Postoperative complications partially account for the association.